Cancer risks in rheumatoid arthritis patients who received immunosuppressive therapies: Will immunosuppressants work? - Zhang, Yuzhuo; Lin, Jiangpeng; You, Zhixuan; Tu, Hengjia; He, Peng; Li, Jiarong; Gao, Rui; Liu, Ziyu; Xi, Zhiyuan; Li, Zekun; Lu, Yi; Hu, Qiyuan; et al. (Frontiers in Immunology, 2022)
Background Exploring the cancer risks of rheumatoid arthritis (RA) patients with disease-modifying anti-rheumatic drugs (DMARDs) can help detect, evaluate, and treat malignancies at an early stage for these patients. Thus, a comprehensive analysis was conducted to determine the cancer risk of RA patients using different types of DMARDs and analyze their relationship with tumor mutational burdens (TMBs) reflecting immunogenicity. Methods A thorough search of PubMed, EMBASE, Web of Science, and Medline was conducted up to 20 August 2022. Standardized incidence ratios (SIRs) were constructed with a random-effect model to determine risks for different types of malignancies in comparison with the general population. We also analyzed the correlation between SIRs and TMBs using linear regression (LR). Results From a total of 22 studies, data on 371,311 RA patients receiving different types of DMARDs, 36 kinds of malignancies, and four regions were available. Overall cancer risks were 1.15 (SIR 1.15; 1.09–1.22; p < 0.001) and 0.91 (SIR 0.91; 0.72–1.14; p = 0.402) in RA populations using conventional synthetic DMARDs (csDMARDs) and biologic DMARDs (bDMARDs), respectively. RA patients taking csDMARDs displayed a 1.77-fold lung cancer risk (SIR 1.77; 1.50–2.09; p < 0.001), a 2.15-fold lymphoma risk (SIR 2.15; 1.78–2.59; p < 0.001), and a 1.72-fold melanoma risk (SIR 1.72; 1.26–2.36; p = 0.001). Correlation coefficients between TMBs and SIRs were 0.22 and 0.29 from those taking csDMARDs and bDMARDs, respectively. Conclusion We demonstrated a cancer risk spectrum of RA populations using DMARDs. Additionally, TMBs were not associated with elevated cancer risks in RA patients following immunosuppressive therapy, which confirmed that iatrogenic immunosuppression might not increase cancer risks in patients with RA. Interpretation Changes were similar in cancer risk after different immunosuppressive treatments, and there was a lack of correlation between SIRs and TMBs. These suggest that we should look for causes of increased risks from the RA disease itself, rather than using different types of DMARDs.